Macrophage heterogeneity in atherosclerosis regression - Fisher, Edward (Henry Stewart Talks, 2012)
Novel research tools, Developing mouse models to study atherosclerosis regression, Developing the tools to analyze macrophage trafficking and molecular phenotypes in vivo, The regression of atherosclerosis by HDL due to its effects on the quantity and phenotype of macrophages in plaques, Macrophage polarization, Plasticity during atherosclerosis regression, Models for the enrichment in cells in the M2 state